If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + u = 7 Reorder the terms: u + 3x = 7 Solving u + 3x = 7 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3x' to each side of the equation. u + 3x + -3x = 7 + -3x Combine like terms: 3x + -3x = 0 u + 0 = 7 + -3x u = 7 + -3x Simplifying u = 7 + -3x
| 3a-16=31 | | 5(1-x)=-5(6x-6) | | 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k |